The Effect Of Liquidity, Solvency, And Profitability On Financial Distress: An Empirical Study On Transportation Sector Companies In The Beige - Pasaribu, Sophia Harnita; Debbie Christine (FEB-Telkom University Publisher, 2025)
This study aims to analyze the influence of liquidity, solvency, and profitability on financial distress in transportation sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. Utilizing logistic regression method with a sample of 45 companies, the study finds that liquidity and profitability have a significant negative effect, while solvency has a significant positive effect on the probability of financial distress. The analysis shows that increases in current ratio and return on assets reduce the risk of financial distress, while an increase in debt to equity ratio elevates this risk. Company size is also found to have a significant negative effect on financial distress. These findings have important implications for financial risk management in the transportation sector, emphasizing the importance of maintaining a balance between liquidity, capital structure, and profitability to enhance companies' financial resilience. This research contributes to a more comprehensive understanding of factors affecting the financial health of transportation companies in Indonesia and provides valuable insights for managerial decision-making and sector policy.